Positive Psychological Coaching Definitions and Models: A Systematic Literature Review - van Zyl, Llewellyn E.; Roll, Lara C.; Stander, Marius W.; Richter, Stefanie (Frontiers in Psychology, 2020)
Despite the popularity of the term Positive Psychological Coaching within the literature, there is no consensus as to how it should be defined (framed) or what the components of a positive coaching “model” should include. The aim of this systematic review was to define positive psychological coaching and to construct a clear demarcated positive psychological coaching model based on the literature. A systematic literature review led to the extraction of 2252 records. All records were screened using specific inclusion/exclusion criteria, which resulted in the exclusion of records based on duplicates (n=1232), titles (n=895), abstracts (n=78) and criteria violations (n=23). Twenty-four academic, peer-reviewed publications on positive psychological coaching were included. Data relating to conceptual definitions and coaching models/phases/frameworks were extracted and processed through thematic content analysis. Our results indicate that positive psychological coaching can be defined as a short to medium term professional, collaborative relationship between a client and coach, aimed at the identification, utilization, optimisation and development of personal strengths and resources in order to enhance positive states, traits and behaviours. Utilizing Socratic goal setting and positive psychological evidence-based approaches to facilitate personal growth, optimal functioning, enhanced wellbeing and the actualization of people’s potential. Further, eight critical components of a positive psychological coaching model were identified and discussed. The definition and coaching process identified in this study will provide coaches with a fundamental positive psychological framework for optimising people’s potential.